NATURAL DEVELOPMENT OF UBIQUITOUS INTERFACES. - Berti, Silvia; Paternò, Fabio; Santoro, Carmen (Communications of the ACM, 2004)
A goal of natural development is to ease the building of interactive software systems. Some work has been dedicated to obtaining natural pros gramming [3], which aims to support programming through languages understandable by people without any specific programming skills. On one hand, natural development implies that people should be able to work through familiar and instantly understandable representations that allow them to easily express relevant concepts, and thereby create or modify applications. On the other hand, since a software artifact must be precisely specified in order to be implemented, there will still be the need for environments supporting transformations from intuitive and familiar representations into precise but more difficult to develop descriptions.